Scleral Fixation of Toric Intraocular Lens in the Absence of Capsular Support - Karolina Krix-Jachym; Natalia Błagun; Marek Rękas (Case Reports in Ophthalmological Medicine)
The study is aimed at describing a technique for scleral fixation of toric intraocular lens (TIOL) in the eyes without capsular support coexisting with corneal astigmatism. A monofocal toric hydrophobic lens with eyelets at the optic-haptic junction (enVista One-Piece Hydrophobic Acrylic MX60T Toric IOL; Bausch & Lomb) was fixated to the sclera using two fragments of 6–0 polypropylene monofilament, the ends of which were brought out through the sclera and cauterized. The astigmatic axis of a TIOL was adjusted according to the corneal astigmatic axis of the patient. The surgery was performed in the 5 eyes of 5 patients without capsular support. The method was safe and effective in fixing the lens to the sclera, and it ensured good centration of TIOL with predictable refractive outcomes. No conjunctival sutures, glue, or flap formation was required during the surgery. There were no relevant complications related to the procedure.